ANALISIS KINERJA KEUANGAN PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI OTORITAS JASA KEUANGAN SEBELUM DAN SELAMA PEMERINTAHAN PRESIDEN JOKOWI - Firqatun Nafilah; Mohammad Amin; Muhammad Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTThis study aims to determine the differences in the financial performance of Real Estate and Property companies before and during President Jokowi's administration. The population in this study is a company registered with the Financial Services Authority. The sample used is a Real Estate and Property company. The technique used in sampling is the Purposive Sampling technique, the sample selected was 20 companies. Data is taken using the documentation method. This study was analyzed using the Paired Samples T-test analysis tool. Before testing the difference in the two average values, the normality test using the One Samples Kolmogorov-Smirnov Test method is carried out beforehand, this test is done using the SPSS program application. The results of the Paired Samples T-test study there are three variables, namely Current Ratio (CR), Assets Turnover (AT), Return On Assets (ROA) that experience differences. While the variables Debt to Total Asset Ratio (DAR) and Return On Equity (ROE) did not experience differences before and during President Jokowi's administration. Keywords: paired samples t-test, financial performance, property and real estate